Where women of color thrive in STEM: institutional factors and how departmental practices indicate shared values - Changstrom, Jessica R. (Kansas State University, 2022)
This research is a part of an international collaboration titled Centering Women of Color in STEM. Women of color have been historically excluded from STEM fields. The goal of this larger project is to investigate where women of color are thriving in STEM. To do this, we analyzed 12 years of IPEDS data encompassing 77,975 physics graduates at 742 institutions, 275,941 math graduates at 1279 institutions, and 655,082 computer science graduates at 1426 institutions. From this data, we calculated effectiveness scores to facilitate comparison between institutions. We next elicited common narratives about where women of color earn bachelor’s degrees in physics and compared those narratives to the physics women of color effectiveness score. We looked for shared characteristics among institutions where women of color tend to earn physics degrees, such as geographic location, institutional size, and mission. Physics departments in minority serving institutions and women’s colleges tend to graduate proportionally more women of color, even after controlling for institutional racial and gender demographics, than primarily white co-educational institutions. Other common narratives related to institution size, location, and Carnegie Classification are not supported by the data, suggesting that departmental factors should be investigated. As a first step in investigating departmental factors, we used a communities of practice framework to explore how departments value different constituent groups, focusing on faculty, undergraduate, and graduate students. Through a collaborative, autoethnographic, contrastive case study of two physics departments, we analyzed the inter- and intra-constituency interactions and shared practice of each community demonstrating how each department centers or peripheralizes constituent groups. We argue that how each department enacts their community of practice demonstrates a foundational shared value: faculty autonomy for one and pastoral care of undergraduates for the other. Finally, we performed exploratory case studies of physics departments using data from their websites. We examined two cases: physics departments with high women of color effectiveness scores and physics, math, and computer science departments at the same institution with contrasting women of color effectiveness scores. Using conjecture mapping, we used our earlier results and literature to create a rubric for analyzing these websites. We see commonalities in the websites of departments that scored high including a focus on undergraduate research and career preparation. This exploratory work will help inform future case studies of high scoring departments.
Keywords: Women of color in STEM; Women of color in physics; Physics culture